PENGARUH HEDONIC SHOPPING VALUE DAN SHOPPING LIFE STYLE TERHADAP IMPULSE BUYING PADA PELANGGAN TOKOPEDIA DI DESA TABA LAGAN BENGKULU TENGAH - Febriana Astita; Adi Sismanto (UM. Bengkulu, 2026)
The research on Tokopedia customers in Taba Lagan Village, Central Bengkulu, addresses the problem formulation of the influence of Hedonic Shopping Value (X1) and Shopping Lifestyle (X2) on Impulse Buying (Y) among Tokopedia customers in Taba Lagan Village, Central Bengkulu. The objective of this research is to determine the influence of Hedonic Shopping Value and Shopping Lifestyle on Impulse Buying among Tokopedia customers in Taba Lagan Village, Central Bengkulu. The population used in this study consists of all Tokopedia customers in Taba Lagan Village, Central Bengkulu, totaling 140 respondents. The sampling technique used is (Hair, 2019) based on certain established criteria amounting to 140 respondents. Data collection techniques include observation, documentation, and questionnaires. The processed data was analyzed using the SPSS 24 formula. Based on the results of the research and the analysis of the influence of the Hedonic shopping value (X1) and Shopping lifestyle (X2) on Impulse Buying among Tokopedia customers in Taba Lagan Village, Central Bengkulu, the following conclusions can be drawn: Hedonic shopping value (X1) has a positive and significant effect on Impulse Buying (Y) of consumers at Tokopedia customers in Taba Lagan Village, Central Bengkulu, as evidenced by the hypothesis test with the t-test showing thitung > ttabel (2.509 > 1.977). Shopping lifestyle (X2) has a positive effect on Impulse Buying (Y) of consumers at Tokopedia customers in Taba Lagan Village, Central Bengkulu. This is evidenced by hypothesis testing using the t-test where the calculated t is greater than the table (2.673 > 1.977). Hedonic shopping value (X1), shopping lifestyle (X2), functional value (X3), and social value (X4) influence consumers' impulse buying (Y). This can be established from the simultaneous hypothesis test where the F table is greater than the calculated F (12.749 > 3.910). This is supported by a correlation analysis of R = 0.802 (80.2%), which is close to 1. Additionally, the coefficient of determination is R² = 0.643 or about 64.3%, while 35.7% is the contribution from other variables that are not studied. Keywords: Hedonic Shopping Value and Shopping Lifestyle Impulse Buying.